PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 005 RAJA BEJAMU KECAMATAN SINABOI KABUPATEN ROKAN HILIR - ', Nurbaini; ', Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : to the effect this research is subject to be know if learning model implement kooperatif think pair shere (TPS) can increase IPS studying result student class IV in SD Negeri 005 Raja Bejamu. This observational type is Observational Action braze (PTK) with subjek penleitian student brazes IV. which total 20 students. Data collecting tech that is utilized is observation and essay. Result observationaling to conclude that IPS'S learning by use of model pemblajaran kooperatif TPS can increase teacher and student activity and IPS studying result. On first cycle appointment i. activity percentage learns is 66,67% by good categories, on appointment second becomes 75.00%. First cycle appointment II., activity that researcher does increase to become 83,33%. second cycle appointment II., activity that researcher does reach 87,50% by good peer categories. Then for student activity On first meet student activity percentage 62.5% by good categories, appointment second becomes 70.83% by good categories. On cycle II. first activity appointment student increases becoming 79.17% by good categories and on second appointment, step-up becomes 83.33% by good peer categories. Learned yielding step-up IPS Student also experience step-up, on thoroughnesses base score klasikal not complete 42.85% worked up on i. cycle as 61.90% by categories not complete, on cycle II. worked up again as 78.57% by complete categories.Key word : TPS model, IPS Learned result